Experimental investigation of lubricant film thickness in an automotive final drive unit. - Fusco, Lucia (Cranfield University, 2013)
Society has been aware of the environmental impact of vehicles for some time now, with governments trying to control and reduce this impact by introducing emissions standards to control pollutants as well as CO₂ emissions. One way in which total emissions can be reduced is by increasing the efficiency of vehicles as a whole, resulting in greater fuel economy. Related to increased transmission efficiency, lubricant flow within a final drive unit (FDU) was researched, enabling a better understanding of the system through visualisation and laser induced fluorescence (LIF) measurements. A LIF measurement technique has been developed, along with a quantitative wedge calibration method, to measure lubricant thicknesses within a Jaguar Land Rover X150 FDU. The measurements and data recorded in this thesis are taken from an original clear-cased replica FDU, which proved to be suitable for visualisation and LIF measurements. The results show lubricant thickness trends are dependent on the fill volume and rotational speed of the gear. The measured peak lubricant thickness on the carrier- and cover-side of the crown wheel increased with fill volume. As the fill volume increased, the amount of lubricant entrained by the crown wheel increased, resulting in the increased lubricant thickness. As the equivalent vehicle road speed increased to approximately 8mph, the measured lubricant thickness increased to its maximum value of 1.75mm for a fill volume of 900ml. From 8mph onwards, the lubricant thickness was found to decrease again to less than 0.1mm at around 10mph. Up to 8mph, gravity appeared to be the overriding influence, pulling the lubricant from the crown wheel. At 8mph, these forces seemed to be in balance, resulting in the greatest measured lubricant thickness. Above 8mph, the force from the gear rotation ejected lubricant from the crown wheel. Gathered data and relationships provide new quantitative metrics for measurement and enhanced understanding of lubricant movement within the FDU. The methodology and equipment developed here for studying the FDU are suitable for wider use in any geared or lubricated system.
Keywords: Transmission efficiency; lubricant flow; laser induced fluorescence (LIF); quantitative wedge calibration; fill volume; rotational speed